2009
DOI: 10.1126/science.1175065
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ligase TRAF6 Regulates Akt Ubiquitination and Activation

Abstract: Akt signaling plays a central role in many biological functions, such as cell proliferation and apoptosis. Since Akt resides primarily in the cytosol, it is not known how these signaling molecules are recruited to the plasma membrane and subsequently activated by growth factor stimuli. Here, we found that the protein kinase Akt undergoes lysine 63 chain ubiquitination, which is important for Akt membrane localization and phosphorylation. TRAF6 was found to be a direct E3 ligase for Akt and was essential for Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
606
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 546 publications
(642 citation statements)
references
References 28 publications
20
606
1
1
Order By: Relevance
“…Ubiquitin can be covalently attached to the lysine residues of target proteins by E3 ubiquitin ligase (Sun, 2006) and itself can also be ubiquitinated at Lys48 or Lys63 to form poly-ubiquitin chains (Ravid and Hochstrasser, 2007;Yang et al, 2009). Target proteins labeled with Lys48 poly-ubiquitination chains usually are recognized and degraded by the proteasome system (Pickart, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin can be covalently attached to the lysine residues of target proteins by E3 ubiquitin ligase (Sun, 2006) and itself can also be ubiquitinated at Lys48 or Lys63 to form poly-ubiquitin chains (Ravid and Hochstrasser, 2007;Yang et al, 2009). Target proteins labeled with Lys48 poly-ubiquitination chains usually are recognized and degraded by the proteasome system (Pickart, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…57 Finally, AKT undergoes TRAF6-catalyzed K63-type ubiquitination at the PH domain upon exposure to growth factor, which promotes AKT membrane adherence, phosphorylation and activation without influencing its phosphatidylinositol (3,4,5)-trisphosphate lipidbinding capability. 58 Recent data showed that the activity of ULK1 is also regulated by ubiquitination. In cells undergoing autophagy, AMBRA1, a binding partner for both Beclin-1 and ULK1, in complex with TRAF6 supports K63-linked polyubiquitination and consequent self-association, stabilization and activation of ULK1.…”
Section: Involvement Of the Ubiquitin System In Antimicrobial Autophagymentioning
confidence: 99%
“…Akt activation is initiated by membrane recruitment, mainly through its PH domain-mediated phospho-lipid binding, 2 or in part through K63-linkage ubiquitination. 3 Membrane attachment subsequently induces a structural change to facilitate the phosphorylation of two critical residues: T308 in the Akt1 catalytic domain by PDK1 and S473 in the C-terminal hydrophobic motif by mTORC2 (also termed PDK2) for full Akt activation. Subsequently, activated Akt exerts its physiological functions by phosphorylating a wide spectrum of substrates.…”
mentioning
confidence: 99%